2014
DOI: 10.1002/cam4.212
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and survival of HPV‐related tonsillar carcinoma

Abstract: The aim of this study was to determine the proportion of human papilloma virus (HPV)-positive cases in tonsillar carcinomas and investigate its development over the last decade. Further aim was to show the oncologic results in accord to HPV status and various treatment modalities. A retrospective study was conducted between 2000 and 2012 and included 275 patients treated for tonsillar carcinoma. P16 immunohistochemistry was used as a surrogate marker for HPV-associated carcinogenesis. A total of 101 (36.7%) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Though improving significantly, the current life expectancy in Mozambique is 52 years [21]. A recent study from Germany evaluating 275 patients with tensile cancer demonstrated a median age of 56 and 59 for p16 positive and negative tumors, respectively [22]. An evaluation of the burden of potentially HPV associated OP and OC cancers in the US showed only 3% of tonsil tumors present before 40 years of age [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though improving significantly, the current life expectancy in Mozambique is 52 years [21]. A recent study from Germany evaluating 275 patients with tensile cancer demonstrated a median age of 56 and 59 for p16 positive and negative tumors, respectively [22]. An evaluation of the burden of potentially HPV associated OP and OC cancers in the US showed only 3% of tonsil tumors present before 40 years of age [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our data’s average age coincided with both of these studies (59y for OP and 52y for OT), but a significant portion of people in Mozambique, may not live long enough to develop this cancer. Secondly, the report from Germany noted 80% of the p16 positive tumors presented as T1 or T2 tumors [22]. In discussions with otolaryngologists in Maputo, many patients who do present to the hospital with head and neck cancers do so at such a late stage that biopsy is often not performed and patients are generally palliated with a tracheosotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of oropharyngeal carcinomas diagnosed today is related to a previous human papillomavirus (HPV) infection . HPV‐positive tumors represent a distinct category with specific biology and oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade the incidence of HPV related OPCs have doubled in number of patients and therefore more attention has drawn to these cancer types. [114] HPV positive oropharyngeal cancers are mainly associated with oral sex and rare p53 mutation. [115] Interestingly HPV infection was shown to improve the prognosis of OPC with better survival is reported in HPV positive OPCs [116] and therefore these patients may have a chance to benefit from a less intense treatment strategy.…”
Section: Head and Neck Carcinomasmentioning
confidence: 99%